1998
DOI: 10.1183/09031936.98.11040949
|View full text |Cite
|
Sign up to set email alerts
|

The role of ICAM-1 on T-cells in the pathogenesis of asthma

Abstract: The capacity of inflammatory cells to adhere is critical to inflammatory responses and involves an array of adhesion molecules grouped into distinct families. Intercellular adhesion molecule (ICAM)-1 has recently attracted much interest in view of increasing evidence that it plays a prominent role in allergic diseases such as asthma and rhinitis. Apart from its role in adhesion of inflammatory cells to vascular endothelium, the extracellular matrix and epithelium, ICAM-1 mediates T-cell/T-cell, T-cell/target c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 96 publications
3
66
0
4
Order By: Relevance
“…[21][22][23] The interaction of αL/β2 integrin and ICAM-1 is also a target for the treatment of allergic diseases. 23,24) Eosinophil and T cell infiltration recorded in the lungs of Th2 cell-transferred mice in this study generally supports previous research, but the contribution of α4/β1 was not observed. As the adhesion molecule network is highly redundant (Figs.…”
Section: )supporting
confidence: 80%
See 1 more Smart Citation
“…[21][22][23] The interaction of αL/β2 integrin and ICAM-1 is also a target for the treatment of allergic diseases. 23,24) Eosinophil and T cell infiltration recorded in the lungs of Th2 cell-transferred mice in this study generally supports previous research, but the contribution of α4/β1 was not observed. As the adhesion molecule network is highly redundant (Figs.…”
Section: )supporting
confidence: 80%
“…These contradictory findings might be caused by the participation of remaining receptors/ligands, such as ICAM-2, ICAM-3, and αM. 24) Furthermore, we previously showed that a fraction of infused T cells spontaneously distributed in the lungs before antigen provocation rather than those migrated in response to the antigen plays a primary role in the development of lung inflammation. 13) This might explain the lack of suppression of neutrophil accumulation regardless of the significant inhibition of Th1 cells by anti-αL and -β2.…”
mentioning
confidence: 99%
“…ICAM-1 mediates cell to cell adhesion and has been shown to play an important role in several diseases including asthma, atherosclerosis, autoimmune disease, ischemia reperfusion injury and acute respiratory distress syndrome. [40][41][42][43][44] ICAM-1 has also been shown to be involved in lung cancer cell invasion, 45 and since elevated levels of ICAM-1 expression has been associated with increased metastasis and poor prognosis in cancer, 46 it is being extensively studied as an important target in cancer therapy. Inhibition of ICAM-1 expression could be a useful tumor response biomarker and also a useful Nutlin-3 Downregulates NFκB Pathway target to decrease metastasis in lung cancer and also potentially other cancers where ICAM-1 levels are elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, virus-activated T cells induce shedding of ICAM-1, and circulating sICAM-1 is suggested to be a sensitive marker of T-cell activation in choriomeningitis (Christensen et al 1995). Because intercellular adhesion molecule (ICAM)-1 is the receptor for a major group of RVs (Greve et al 1989), binding of RV to ICAM-1 on T-cells is thought to activate the T-cell function (Stanciu and Djukanovic 1998). Up-regulation of ICAM-1 could increase susceptibility to major group RVs (Greve et al 1989) and lead cells adjacent to infected cells to infection when viruses are released from the cells originally infected.…”
Section: Discussionmentioning
confidence: 99%